Protected areas in regions of intensive economical activity: conflict of nature protection and nature use (case study of Dovine river catchment) - Linkevičienė, Rita; Taminskas, Julius; Šimanauskienė, Rasa (Acta Geographica Debrecina Landscape & Environment series, 2007)
Nature protection and economical activity clash of interests is analysed on the example of Dovinė River catchment, situated in the south western part of Lithuania. It is a unique wetland complex consisting from Žuvintas Lake and the surrounding bogs (Fig. 1). Žuvintas Lake became the first protected area in Lithuania in 1937. However, the lake is situated in one of the most fertile region of Lithuania, where the methods of intensive farming activity is being employed for a long time. Eutrophication processes and overgrowth of this shallow lake has been very active during the several decades and the lake has lost its ecological value. Therefore the main goal of this article is to analyse the anthropogenic influence towards the water bodies and protected natural values situated in the territory of intensive economical activity. Cartographical material of different periods is being used for the evaluation of the hydrographical network transformations in Dovinė River catchment. Hydrochemical parameters of the periods 1953–1954, 1960–1961, 1980–1982; 1993–2003; 2004–2005 of the water bodies in Dovinė River catchment are being analysed. The field works in order to investigate the water quality in Dovinė River and it‘s tributaries were made in spring of 2005. Water samples were analysed in laboratory of the Institute of Geology and Geography according water quality analysis methods approved by Lithuanian Ministry of Environment (Table 2). Water quality was evaluated according maximum residue limits (MRL) in surface waters (Table 3). The results of the study showed that although Žuvintas Lake is being protected for 70 years, the farming activity intensified constantly in its catchment. Canalised river beds and sluice–regulated hydrological regime of the lakes diminished the natural self–cleaning abilities of the water system. The average annual decrease of the lake specular surface was about 1,1 ha in the period of 1961–2003. The average annual increase of vegetation area is about 0,14 ha. Even a strong protection regime did not preserve this territory. Therefore, in order to keep the sustainable development in the protected territories the anthropogenic loading from the neighbouring territories (catchment area, etc) must be evaluated. The objectives of nature protection in protected territory could not be attained if there is no regulation of economical activity in the territories surrounding the protected area.